2015
DOI: 10.1097/mpa.0000000000000500
|View full text |Cite
|
Sign up to set email alerts
|

Acute Pancreatitis—Progress and Challenges

Abstract: An international symposium entitled “Acute pancreatitis: progress and challenges” was held on November 5, 2014 at the Hapuna Beach Hotel, Big Island, Hawaii, as part of the 45th Anniversary Meeting of the American Pancreatic Association and the Japanese Pancreas Society. The course was organized and directed by Drs. Stephen Pandol, Tooru Shimosegawa, Robert Sutton, Bechien Wu, and Santhi Swaroop Vege. The symposium objectives were to: (1) highlight current issues in management of acute pancreatitis, (2) discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(41 citation statements)
references
References 149 publications
(155 reference statements)
0
40
0
1
Order By: Relevance
“…Results of the systematic review and a list of candidate parameters for inclusion in the score have been previously reported (8). From an initial review of 345 abstracts, we identified 69 studies that met full inclusion and exclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of the systematic review and a list of candidate parameters for inclusion in the score have been previously reported (8). From an initial review of 345 abstracts, we identified 69 studies that met full inclusion and exclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…To identify items for potential inclusion in the activity score we performed a systematic literature review of clinical outcome and assessment measures used in previous randomized controlled trials in acute pancreatitis (8). Specifically, we conducted a search of PubMed, Embase and the Cochrane database of studies published from 1996 to 2014 that met the following criteria: randomized control trials, English language, use of Human subjects, and studies that evaluated the effect of therapy in acute pancreatitis.…”
Section: Methodsmentioning
confidence: 99%
“…The development of pharmacologic and other therapy for acute pancreatitis requires the demonstration of quantifiable improvement in clinical outcomes [19]. Given its correlation with multiple aspects of the clinical course of pancreatitis, PASS represents a promising tool to gauge responses to therapy as well as to assess for the resolution of disease.…”
Section: Discussionmentioning
confidence: 99%
“…[ 43 ] Early severity assessment is important, especially in the first 48 hours of admission with respect to the window of opportunity for using interventions to prevent necrosis. [ 44 ] However, some parameters, such as the CRP, need more than 48 hours to reach a peak value, which may influence the diagnostic accuracy. Even with its delayed increase and peak, CRP remains useful and widely available.…”
Section: Discussionmentioning
confidence: 99%